Intermuscular Two‐Incision Technique for Subcutaneous Implantable Cardioverter Defibrillator Implantation: Results from a Multicenter Registry. Issue 3 (10th February 2017) - MIGLIORE, FEDERICO; ALLOCCA, GIUSEPPE; CALZOLARI, VITTORIO; CROSATO, MARTINO; FACCHIN, DOMENICO; DALEFFE, ELISABETTA; ZECCHIN, MASSIMO; FANTINEL, MAURO; CANNAS, SERGIO; ARANCIO, ROCCO; MARCHESE, PROCOLO; ZANON, FRANCESCO; et al.
Abstract : Background: The traditional technique for subcutaneous implantable cardioverter defibrillator (S‐ICD) implantation, which involves three incisions and a subcutaneous pocket, is associated with possible complications, including inappropriate interventions. The aim of this prospective multicenter study was to evaluate the efficacy and safety of an alternative intermuscular two‐incision technique for S‐ICD implantation. Methods: The study population included 36 consecutive patients (75% male, mean age 44 ± 12 years [range 20–69]) who underwent S‐ICD implantation using the intermuscular two‐incision technique. This technique avoids the superior parasternal incision for the lead placement and consists of creating an intermuscular pocket between the anterior surface of the serratus anterior and the posterior surface of the latissimus dorsi muscles instead of a subcutaneous pocket. Results: All patients were successfully implanted in the absence of any procedure‐related complications with a successful 65‐J standard polarity defibrillation threshold testing, except in one, who received a second successful shock after pocket revision. During a mean follow‐up of 10 months (range 3–30), no complications requiring surgical revision were observed. At device interrogation, stable sensing without interferences was observed in all patients. Two patients (5.5%) experienced appropriate and successful shock on ventricular fibrillation and in four patients (11%), a total of seven nonsustained self‐terminated ventricular tachycardias were correctly detected. No inappropriate interventions were observed. Conclusions: Our experience suggests that the two‐incision intermuscular technique is a safe and efficacious alternative to the current technique for S‐ICD implantation that may help reducing complications including inappropriate interventions and offer a better cosmetic outcome, especially in thin individuals.